1994
DOI: 10.1159/000133796
|View full text |Cite
|
Sign up to set email alerts
|

Expression level of <i>Rps4 </i>mRNA in 39, X mice and 40, XX mice

Abstract: Contrary to the effects of X-chromosome monosomy in humans (Turner syndrome), XO mice are fertile and anatomically normal. The human RPS4X gene encodes ribosomal protein S4 and escapes X-chromosome inactivation, and its haploinsufficiency has been suspected to contribute to Turner syndrome. Therefore, we compared the expression level of mRNA of Rps4 (the mouse homolog of RPS4X) between XX and XO mice using Northern blot analysis. The XO/XX ratio of Rps4 mRNA obtained from Northern blot analysis was 0.9. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The X chromosome genes responsible for congenital heart defects in TS have not been identified, and the lack of a suitable animal model for TS has been a significant limitation. The absence of overt TS phenotypes in female mice with a single X chromosome may be attributable to differences in X inactivation or X chromosome gene content between mice and humans [Omoe and Endo, ]. The purpose of this collaborative genomic study was to investigate the effect of X chromosome gene content and common variation on congenital heart defects in TS women.…”
Section: Introductionmentioning
confidence: 99%
“…The X chromosome genes responsible for congenital heart defects in TS have not been identified, and the lack of a suitable animal model for TS has been a significant limitation. The absence of overt TS phenotypes in female mice with a single X chromosome may be attributable to differences in X inactivation or X chromosome gene content between mice and humans [Omoe and Endo, ]. The purpose of this collaborative genomic study was to investigate the effect of X chromosome gene content and common variation on congenital heart defects in TS women.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed to be due to the presence in humans and absence in mice of haploinsufficiency of presumed Turner-phenotype genes (RPS4X/Rps4, ZFX/Zfx) (Ashworth et al. 1991;Zinn et al, 1991 ;Omoe and Endo, 1994). However, it has been shown that the ratio of XX to XO embryos (XX:XO) is about 2:1 in the female offspring of the XO mouse colony.…”
mentioning
confidence: 99%
“…The human RPS4 (ribosomal protein S4) gene is responsible for the onset of Turner syndrome because it is biallelically expressed under normal conditions [21]. In contrast, its mouse homologue, Rps4, is a gene subject to X chromosome inactivation, and its function is assured by the presence of a single allele [22]. Little information about the occurrence of XO females is available for other species, but the laboratory mouse is not the only species known to produce normal XO females.…”
Section: Resultsmentioning
confidence: 99%